Implementasi Algoritma Simple Additive Weighting dalam Perangkingan Seleksi Penerimaan Peserta Didik Baru Tingkat SD & SMP di Dinas Pendidikan Kota Lubuklinggau - Auliya, Muhammad Noval Nur; Hidayati, Tri (Scientia Sacra: Jurnal Sains, Teknologi dan Masyarakat, 2023)
Lubuklinggau City is one of the regions/cities that implements New Student Admissions, hereinafter abbreviated PPDB offline. The PPDB is carried out directly by the Education and Culture Office, hereinafter abbreviated as Lubuklinggau City Education and Culture Office. The Education and Culture Office of Lubuklinggau City only oversees the PPDB at the basic education level, namely elementary and junior high schools. From year to year the schools in Lubuklinggau City use paper forms in implementing PPDB so that when collecting data by the Lubuklinggau City Office of Education, they experience difficulties in integrating data between schools as a result, many data that is out of sync with each other. Apart from that, quite a lot of time and money is needed in implementing PPDB to data processing by the Education and Culture Office of Lubuklinggau City. Transparency to the public regarding PPDB ranking results is also a separate obstacle for the Lubuklinggau City Education and Culture Office because the data is not yet centralized, making it difficult for the Lubuklinggau City Education and Culture Office to monitor the data in real time. Every year it raises the same problem for each PPDB implementing school, namely the existence of data on student applicants who double enroll in different schools so that it makes students attractive in fulfilling school quotas, because there is no integrated and centralized database. So that it is detrimental for some small schools whose student quotas are reduced due to the double student data problem. Based on these considerations, the authors try to provide alternative solutions to problems that occur by creating a system that can help create an integrated database for the Education and Culture Office and schools in Lubuklinggau City in implementing PPDB, helping to make time and cost efficiency in implementing PPDB, minimizing the use of paper such as filling out forms and others, helps transparency of values in ranking to the public in real time, avoids data on student applicants who are accepted at schools with double goals, equal distribution of students with the zoning system, registration is more orderly and easily monitored by the agency and the public.